THU0033 RNA PROFILING OF HEALTHY AND RHEUMATOID ARTHRITIS SUBJECTS TREATED WITH TOFACITINIB MONOTHERAPY. (June 2019) - Hadjipanayis, Angela; Chen, Xing; Lee, Julie; Zhao, Shanrong; Zhang, Weidong; Martin, David; Maciejewski, Mateusz; Ziemek, Daniel; Fitz, Lori; Hyde, Craig; Schack, David von
Abstract : Background: The Janus kinase (JAK) family of tyrosine kinases includes JAK1, JAK2, JAK3 and TYK2 which signals through type I and type II cytokine receptors. Tofacitinib is an oral JAK inhibitor approved for the treatment of rheumatoid arthritis (RA). In cellular settings where JAKs signal in pairs, tofacitinib preferentially inhibits signalling by heterodimeric receptors associated with JAK1 and/or JAK3 and has functional selectivity over JAK2. Next generation sequencing (i.e. RNA sequencing) offers an unbiased analysis of whole transcriptome pharmacology. Objectives: To profile the transcriptome in whole blood samples collected in a Phase 1 healthy volunteer (HV) study and a Phase 2 study with RA subjects treated with placebo, 5 mg, 10 mg or 15 mg of tofacitinib monotherapy. Methods: In the HV study, a total of 93 Paxgene RNA tubes were obtained from 30 subjects collected at screening, at baseline on day 1, and at 2 hours post dosing on day 15. HVs were treated daily with tofacitinib (10 mg BID) for 15 days. In the RA study (NCT00550446 ), a total of 239 RNA samples were obtained from 25–31 subjects at baseline and day 28 who were treated with tofacitinib 5 mg BID, 10 mg BID or 15 mg BID daily for 84 days. RNAseq libraries were generated using a polyA based mRNA kit and sequenced to a depth of ∼40 million paired-end reads. Upstream processing included alignment of sequences, gene quantification and data quality control. The raw reads were normalised using the Trimmed Mean of M values (TMM) method in the edgeR package. Log2 fold-changes (FC) and corresponding false discovery rate (FDR)-adjusted p-values (padj) were calculated using the voom function in the Limma package (vers 3.8) in R 3.5.1. In particular, the correlations between baseline and measurements at each visit per patient were estimated by Limma's duplicateCorrelation function. Genes were considered significant after multiple test correction with FDR, or padj <0.1 within each study. Results: Modulation of the JAK-STAT signalling pathways was observed as exemplified by gene expression differences in cytokine-inducible SH2-containing protein (CISH) (p value=4.64E-41 in the HV study and p value=1.2E-8 in the RA study) and suppressor of cytokine signalling (SOCS2) protein (p value=1.38E-18 in HV study and p value=2.27E-7 in the RA study). Gene expression of CISH, a member of the SOCS family, was decreased from its baseline value at day 15 in HV (FC from baseline=0.18) and at day 28 in RA subjects (FC from baseline=0.42) when comparing tofacitinib treatment (HV:10 mg, RA:15 mg) to baseline or placebo, respectively. SOCS2 gene expression was also decreased at day 15 in HV (FC from baseline=0.40) and at day 28 in RA subjects (FC from baseline=0.52) when comparing tofacitinib treatment (HV:10 mg, RA:15 mg) to baseline or placebo, respectively. Other changes observed in the HV study: 301 genes were upregulated and 169 genes were downregulated when comparing 2 hours post dose on day 15 to baseline. In the RA study, 643 genes were upregulated and 801 genes were downregulated when comparing the 15 mg dose to placebo at week 4. Preliminary pathway level analysis shows overall a broader modulation of cytokine and chemokine signalling pathways by tofacitinib treatment in RA compared to what we observe in HV. Conclusion: The results of this post hoc analysis demonstrate that tofacitinib induces measureable changes in the modulation of the JAK-STAT signalling pathway as well as effects on inflammatory cytokines and chemokines. The existence of overlapping but also unique JAK-STAT pathway inhibition due to tofacitinib between the HV and RA studies, as well as ongoing work, will provide a better understanding of response/non-response to tofacitinib and future drug developments. Disclosure of Interests: Angela Hadjipanayis Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Xing Chen Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Julie Lee Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Shanrong Zhao Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Weidong Zhang Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, David Martin Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Mateusz Maciejewski Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Daniel Ziemek Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Lori Fitz Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Craig Hyde Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, David von Schack Shareholder of: Pfizer Inc, Employee of: Pfizer Inc